The quality of apical preparation in curved root canals using hand and rotary instrumentation techniques - Silveira, Luiz Fernando Machado; Bosembecker, Juliana Kutter; Martos, Josué; Ferrer-Luque, Carmen Maria (Archives of Oral Research, 2011)
Objectives: To determine the quality of apical preparation in mesiobuccal root canals of mandibular molarsusing hand stainless steel K-Flexofile, nickel-titanium rotary ProTaper and ProTaper + ProFile instruments.Materials and methods: Thirty freshly extracted mandibular molars were randomly divided intothree experimental groups (n = 10). The mesiobuccal root canals were prepared with K-Flexofile and GoldenMedium hand files (group 1); with ProTaper (group 2) and with ProTaper + ProFile rotary instruments(group 3). After histological preparation the comparative analysis was performed at 1 mm, 3 mm and 5 mmfrom the working length. Each sample was evaluated on cleaning and shaping based on established criteria.Data were analyzed statistically by the Kruskal Wallis and Mann-Whitney U tests at a 5% significance oflevel. Results: The hand instrumentation group showed significantly better apical quality preparation thanboth rotary instrumentation groups (p < 0.05). The comparison between the two rotary techniques showedno statistical differences (p > 0.05). The buccal and lingual walls of the root canals showed more pulp tissue remnants than mesial or distal walls. Conclusions: None of the three techniques was totally effective incleaning the apical root canal space of mesiobuccal canals of mandibular molars.